HUBUNGAN PERSEPSI PESERTA DIDIK TENTANG MODEL PROJECT CITIZEN DENGAN HASIL BELAJAR ADA MATA PELAJARAN PPKn KELAS VIII DI SMPN 15 KOTA SERANG - Nurdiana Nurdiana; Cucu Atikah; Lukman Nulhakim (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2023)
ABSTRACT The purpose of this study was to describe and analyze the relationship between students' perceptions of the project citizen model and learning outcomes in the Pancasila and Civics Education Class VIII subject at SMPN 15 Serang City. This study uses a quantitative approach with the correlational method. The population in this study were all students of class VIII SMPN 15 Serang City, totaling 263 people and the research sample totaling 40 people. Sampling technique using the Slovin formula. Data collection techniques regarding students' perceptions of the project citizen model use a questionnaire, and data on student learning outcomes using tests. Analysis of the data used is descriptive statistical analysis. The results of the study show that there is a significant relationship (56.40%) students' perceptions of the project citizen model with learning outcomes in Pancasila and Civics Education Class VIII subjects at SMPN 15 Serang City, so it can be concluded that the more positive students' perceptions of the project citizen model are, the The better the Civics learning outcomes for students and vice versa, the less good students' perceptions of the project citizen model will be, the lower the results of Civics learning will be.